Prolonged grief disorder in end-of-life care: current literature and future directions - Gelmez, Pelin Sila; Licht-Handler, Ayala Sara; Naef, Rahel; Lin, Chenchen; Killikelly, Clare (Annals of Palliative Medicine, 2026)
Prolonged grief disorder (PGD) is a recognized distinct mental health disorder in the DSM-5-TR and ICD-11, characterized by core symptoms such as longing for and preoccupation with the deceased that persist and worsen over time. Family members and caregivers of patients that receive end-of-life care are confronted with imminent bereavement, which emphasizes the importance of bereavement care as a preventive measure and the need for continued support after death beyond the hospital setting. This review discusses bereaved family members’ and caregivers’ risk factors of developing PGD, screening and assessment tools (i.e., pre-death measures, measures of bereavement risk, and prolonged bereavement measures) for family members and caregivers of patients during end-of-life care to assess anticipatory loss, after the loss to assess grief reaction, and 6 months after the loss to assess prolonged grief. Implications for accurate and timely interventions during end-of-life care and after the patient’s death are presented. Furthermore, limitations of current assessment methods and interventions, and barriers to and facilitators of guideline implementation are addressed. Early detection of elevated grief symptoms and potential PGD through ecological methods of studying daily life (e.g., Experience-Sampling Method, Electronically Activated Recorder, Mobile Sensing Methods, wearables) and digital, just-in-time interventions personalized to an individual’s needs (i.e., Just-In-Time Adaptive Interventions) present an innovative digital approach for bereavement care in the future.